Beat-to-Beat Variability of Ventricular Action Potential Duration Oscillates at Low Frequency During Sympathetic Provocation in Humans - Porter, Bradley; van Duijvenboden, Stefan; Bishop, Martin J.; Orini, Michele; Claridge, Simon; Gould, Justin; Sieniewicz, Benjamin J.; Sidhu, Baldeep; Razavi, Reza; Rinaldi, Christopher A.; Gill, Jaswinder S.; Taggart, Peter (Frontiers in Physiology, 2018)
Background: The temporal pattern of ventricular repolarization is of critical importance in arrhythmogenesis. Enhanced beat-to-beat variability (BBV) of ventricular action potential duration (APD) is pro-arrhythmic and is increased during sympathetic provocation. Since sympathetic nerve activity characteristically exhibits burst patterning in the low frequency range, we hypothesised that physiologically enhanced sympathetic activity may not only increase BBV of left ventricular APD but also impose a low frequency oscillation which further increases repolarisation instability in humans. Methods and Results: Heart failure patients with cardiac resynchronization therapy defibrillator devices (n=11) had activation recovery intervals (ARI, surrogate for APD) recorded from left ventricular epicardial electrodes alongside simultaneous non-invasive blood pressure and respiratory recordings. Fixed cycle length was achieved by right ventricular pacing. Recordings took place during resting conditions and following an autonomic stimulus (Valsalva). The variability of ARI and the normalised variability of ARI showed significant increases post Valsalva when compared to control (p=0.019 and p=0.032 respectively). The oscillatory behaviour was quantified by spectral analysis. Significant increases in low frequency (LF) power (p=0.002) and normalised LF power (p=0.019) of ARI were seen following Valsalva. The Valsalva did not induce changes in conduction variability nor the LF oscillatory behaviour of conduction. However, increases in the LF power of ARI were accompanied by increases in the LF power of systolic blood pressure (SBP) and the rate of systolic pressure increase (dP/dtmax). Positive correlations were found between LF-SBP and LF-dP/dtmax (rs=.933, p<0.001), LF-ARI and LF-SBP (rs=.681, p=0.001) and between LF-ARI and LF-dP/dtmax (rs=.623, p=0.004). There was a strong positive correlation between the variability of ARI and LF power of ARI (rs=.679, p<0.001). Conclusions: In heart failure patients, physiological sympathetic provocation induced low frequency oscillation (approx. 0.1Hz) of left ventricular APD with a strong positive correlation between the LF power of APD and the BBV of APD. These findings may be of importance in mechanisms underlying stability/instability of repolarization and arrhythmogenesis in humans.